Actin stress fiber organization promotes cell stiffening and proliferation of pre-invasive breast cancer cells - Sandra Tavares (Nature Portfolio, 2017)
When cells acquire a malignant phenotype they become less stiff and this helps migration and invasion favouring metastasis. Here the authors show that Src-driven cell transformation and transition to a less stiff state follows an event of membrane stiffening due to stress fibres accumulation.